DISCLOSURE OF SUSTAINABILITY REPORTS AND INTEGRATED REPORTS HAS AN IMPACT ON COMPANY PROFITABILITY - Hilmi; Marjulin; Muammar Khaddafi; Misratul Izza (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The research aims to determine the impact of the Sustainability Report and Integrated Report on profitability. The Sustainability Report is measured based on the Global Reporting Initiative. The Integrated Report is measured by the nine (9) content elements of the Integrated Report. Profitability is measured using ROA. The population used in this research is mining companies on the BEI in 2016-2020, samples were taken from companies that publish financial reports, annual reports and Sustainability Reports accessed via the company website and the Indonesia Stock Exchange website. The data was analyzed using multiple linear regression techniques. The results of the research show that in the disclosure of the Sustainability Report, of the three (3) dimensions tested, the social dimension has a significant impact on profitability. While the Integrated Report disclosure has no impact on profitability.